The Effect of Dietary Quercetin on the Glutathione Redox System and Small Intestinal Functionality of Weaned Piglets - Jeroen Degroote; Hans Vergauwen; Noémie Van Noten; Wei Wang; Stefaan De Smet; Chris Van Ginneken; Joris Michiels (MDPI AG, 2019)
Quercetin has been shown to alleviate mucosal damage and modulate the glutathione (GSH) redox system in the colon of rodents. In the current study, we assessed whether quercetin was able to mitigate small intestinal dysfunction in weaned pigs. Here, 224 weaned piglets were fed a diet containing quercetin at either 0, 100, 300, or 900 mg/kg diet until d14 post-weaning, followed by a common basal diet until d42. Eight animals per treatment were sampled at d5 and d14 post-weaning. In these animals, the small intestinal histomorphology, barrier function, and protein abundance of occludin, caspase-3, and proliferating cell nuclear antigen were assessed. None of these parameters were affected, and neither did quercetin improve performance up to d42 post-weaning. The GSH redox system was evaluated in blood, small intestinal mucosa, and liver. Quercetin did not affect the glutathione peroxidase, glutathione reductase, and glutamate−cysteine ligase activity in these tissues. In contrast, the hepatic glutathione transferase (GST) activity was significantly increased by quercetin supplementation at d5 post-weaning of 100, 300, and 900 mg/kg. Importantly, d5 was characterized by a more oxidized GSH redox status. To conclude, dietary quercetin had little effect on the small intestine, but did upregulate hepatic GST in the occurrence of redox disturbance.